Public media lobbying: the case of APTS - Ali, Christopher; Forde, Sydney (Frontiers in Communication, 2025)
This paper focuses on the governance structure that links US public television station’s largest federal lobbying firm (America’s Public Television Stations or APTS) with the recently approved ATSC 3.0 broadcast standard, in which APTS is a major advocate. Using a political economic approach to understand the incentives and motivations behind seemingly contradictory APTS lobbying efforts, we interrogate a string of relationships between large industry players and APTS leadership and board members pertaining to ATSC 3.0 adoption. Through an exploration of motivations driven by logics of market-based success that so often praise the pursuit of innovation, we propose that the actual wellbeing of US public broadcasting stations has been sidelined in its own lobbying firm’s efforts to maximize external private profits.